A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East - Tiunova, Tatiana M. (Zootaxa, 2017)
Male, female imagoes and eggs of Paraleptophlebia kunashirica sp. nov. and the larva, male and female imagoes of Paraleptophlebia westoni are described based on material from the Russian Far East. Comparison of the male imago of Paraleptophlebia kunashirica sp. nov. and the larva and male imago of Paraleptophlebia westoni with other known larvae and imagoes of Paraleptophlebia are given. Paraleptophlebia westoni larvae may be distinguished from congeners by characters associated with the mouthparts, such as the ratio of the length of the maxillary and labial palp segments, shape of hypopharynx, and structure of the claw. Male imagoes of Paraleptophlebia kunashirica sp. nov. and Paraleptophlebia westoni сan be distinguished between themselves and other representatives close to them in the form of the ventral appendages and the apex of the penis lobes.